'Anyone but England'? Exploring anti-English sentiment as part of Scottish national identity in sport. (April 2014) - Whigham, Stuart
This article explores the reasons behind the expression of anti-English sentiment by Scots in relation to both sporting and wider social contexts, whilst also considering the impact of migration to England on the attitudes expressed by members of the Scottish diaspora. Drawing upon the conceptual framework of 'narrative identity' proposed elsewhere, data was generated through semi-structured interviews which focused upon the 'ontological' and 'public' narratives of Scottish identity as expressed by Scots living in England. The findings demonstrate the influence of a wide range of personal, social, historical and political factors in highlighting the cleavage between Scotland and England within the context of sport and society, allowing for a more nuanced understanding of the complex relationship between these two nations in the context of sporting rivalry. This relationship is argued to be heavily influenced by the existence of an 'underdog mentality'-style grand 'public narrative' for Scots in relation to their English neighbours, based on perceived differences in economic and sporting resources between the two countries. This 'underdog mentality' therefore acts as a legitimating force for the expression of anti-English sentiment in both a sporting and wider social context as part of some individuals' 'ontological narrative', although the extent of such sentiment was found to vary significantly between individuals and contrasting contexts.